Income diversification among female-headed farming households - Elin Vimefall (Örebro University School of Business, 2015)
In most rural parts of sub-Saharan Africa, production on one's own farm is still the main source of income. However, other sources are becoming more important and obtaining income from outside the agricultural sector has been identified as an important path out of poverty. To take advantage of these more attractive livelihood strategies, households need to overcome several barriers to entry. Female-headed households have been found to have less education, less productive resources, and less access to credit than male-headed households; thus, they have limited options. Using data from the RIGA database, we analyze income diversification among female-headed households in rural Kenya. Using a multinomial logit model, we find that households headed by a married woman are approximately 12 percentage points more likely to rely only on income from their own farms compared to households headed by monogamously married man. Female-headed households are also less likely to diversify into non-agricultural wage work than male-headed households.
Keywords: J16; O12; O15; O55; 330; Income diversification; Livelihood; Female-headed households; Kenya